2017
DOI: 10.1002/1873-3468.12883
|View full text |Cite
|
Sign up to set email alerts
|

Gpn3 is polyubiquitinated on lysine 216 and degraded by the proteasome in the cell nucleus in a Gpn1‐inhibitable manner

Abstract: Gpn1 associates with Gpn3, and both are required for RNA polymerase II nuclear targeting. Global studies have identified by mass spectrometry that human Gpn3 is ubiquitinated on lysines 189 and 216. Our goals here were to determine the type, physiological importance, and regulation of Gpn3 ubiquitination. After inhibiting the proteasome with MG132, Gpn3-Flag was polyubiquitinated on K216, but not K189, in HEK293T cells. Gpn3-Flag exhibited nucleo-cytoplasmic shuttling, but polyubiquitination and proteasomal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Gpn1, Gpn2, and Gpn3 are all essential proteins for cell growth, and deletion of each one results in cell death, suggesting that their functions are not redundant. Interestingly, Gpn1 and Gpn3 in mammalian cells are closely associated for RNAPII biogenesis regarding to protein level stability, mutual dependency, and genetic interaction 21‐24 . In the previous study, we identified yeast NPA3 and GPN3 as two multicopy genetic suppressors of gpn2 ts mutants 14 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gpn1, Gpn2, and Gpn3 are all essential proteins for cell growth, and deletion of each one results in cell death, suggesting that their functions are not redundant. Interestingly, Gpn1 and Gpn3 in mammalian cells are closely associated for RNAPII biogenesis regarding to protein level stability, mutual dependency, and genetic interaction 21‐24 . In the previous study, we identified yeast NPA3 and GPN3 as two multicopy genetic suppressors of gpn2 ts mutants 14 .…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, Gpn1 and Gpn3 in mammalian cells are closely associated for RNAPII biogenesis regarding to protein level stability, mutual dependency, and genetic interaction. [21][22][23][24] In the previous study, we identified yeast NPA3 and GPN3 as two multicopy genetic suppressors of gpn2 ts mutants. 14 In the same screen, we obtained RBA50 as a strong suppressor of gpn2 ts as well, and demonstrated that Rba50 is an essential co-factor of Gpn2 in the process of Rpb3-dependent assembly.…”
mentioning
confidence: 99%